1981
DOI: 10.1099/00221287-124-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Escherichia coli K12 with Defects in Anaerobic Pyruvate Metabolism

Abstract: A strain of Escherichia coli with a mutation in the ana gene was shown to lack acetaldehyde dehydrogenase and alcohol dehydrogenase. The requirement of this strain for an external oxidant to grow anaerobically on glucose shows that the reduction of acetyl-CoA is the principal means of reoxidation of NADH produced during glycolysis in E. coli. Further mutants derived from the ana strain were shown to be affected in the enzymes involved in the fermentation of pyruvate (pyruvate formate-lyase, phosphotransacetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
4

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 8 publications
2
34
4
Order By: Relevance
“…However, although the ana mutant is deficient in ADH under conditions of high catabolite repression, it expresses ADH when grown in the absence of catabolite-repressing sugars (D. P. Clark, unpublished data), i.e., ana is a regulatory mutation closely linked to but not in adh. Furthermore, the ACK-negative mutations of Pascal et al (25) were not at the previously known pta-ack locus but in a new gene, ackB. How these observations relate to the present work is problematical since the nature of the ackB gene is unknown.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…However, although the ana mutant is deficient in ADH under conditions of high catabolite repression, it expresses ADH when grown in the absence of catabolite-repressing sugars (D. P. Clark, unpublished data), i.e., ana is a regulatory mutation closely linked to but not in adh. Furthermore, the ACK-negative mutations of Pascal et al (25) were not at the previously known pta-ack locus but in a new gene, ackB. How these observations relate to the present work is problematical since the nature of the ackB gene is unknown.…”
Section: Resultscontrasting
confidence: 48%
“…Furthermore, Pascal et al (25) found ACK mutants which restored anaerobic growth to an ana (adh) mutant. However, although the ana mutant is deficient in ADH under conditions of high catabolite repression, it expresses ADH when grown in the absence of catabolite-repressing sugars (D. P. Clark, unpublished data), i.e., ana is a regulatory mutation closely linked to but not in adh.…”
Section: Resultsmentioning
confidence: 99%
“…The work presented in this paper has shown that the anaerobic growth with nitrate is truly nitrate respiration. We also showed that B. subtilis is able to grow anaerobically by fermentation of glucose, which is stimulated by pyruvate, in contrast to E. coli, which can ferment either glucose or pyruvate (24). Since pyruvate is produced by fermentation of glucose, the stimulatory effect of pyruvate is puzzling.…”
Section: Discussionmentioning
confidence: 92%
“…In a reexamination of the C. kluyveri Pta workers attempted to detect an acetyl-enzyme intermediate; however, no isotope exchange from labeled acetyl phosphate into either acetyl-CoA or inorganic phosphate was observed in the absence of free CoA, and attempts to isolate an acetyl-Pta intermediate were unsuccessful, which is consistent with a ternary complex mechanism (9). Although numerous genetic and physiological studies have continued to demonstrate the universal function of Pta in acetate metabolism in diverse microbes (1,4,6,8,15,17,24,25,27,30,32,38), mechanistic analyses of the enzyme were abandoned until there was an investigation of Pta from the archaeon Methanosarcina thermophila, which obtains energy for growth by converting acetate to methane (22).Cloning of the gene and heterologous expression of Pta from M. thermophila allowed the large-scale production of protein required for structural studies, biochemical analyses, and the use of site-specific replacement to analyze the function of specific residues (22). Cys 312 was predicted to be present in the active site, although it is not essential for catalysis (31).…”
mentioning
confidence: 99%